EVALUASI PERATURAN DAERAH NOMOR 2 TAHUN 2013 TENTANG GERAKAN MASYARAKAT MAGHRIB MENGAJI DI KABUPATEN KAMPAR - Muhammad Reza Khairullah; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Peoples Movement Maghrib Qur’an in Kampar regency in the last 3 years has not been effective. The availability of teaching staff and public participation in the Community Movement Maghrib Qur’an is one of the causes of the ineffectiveness of the implementation of the Regional Regulation No. 2 of 2013 on the Community Movement Maghrib Qur’an. Interest Regional Regulation No. 2 of 2013 on the Community Movement Maghrib enable Muslims learn the Qur’an and read the Qur’an at the time of maghrib and make the religious community and to get used to reading the Qur'an and had a strong religious character in Kampar regency. From the analysis it was concluded that the Regional Regulation No. 2 of 2013 which is concerning about the Qur’an categorized Maghrib Society Movement has not been successful. This is evident from not achieving the desired goals and objectives of Regulation No. 2 of 2013. As to enable Muslims to learn and read the Qur’an in maghrib time and make the religious community and to get used to reading the Qur’an and has a strong religious character in Kampar regency. Found factors that affect the evaluation of the policy, namely: the availability of faculty and community participation.   Keywords : Evaluation, Community Movement Maghrib Qur’an